Ding Ding : Trams in Hong Kong - Hang, Cathy (Temporary Press, 2023)
Atelier HOKO (2002) is an independent research lab that focuses on the study of the growing disengagement between people, things and space. Founded by Alvin Ho and Clara Koh. This investigation by Cathy Hang in the 'Street Report' publication series looks at the tram system of Hong Kong Island where the author grew up, which is commonly referred to as (3z(BDing Ding(3y(B. The author observes how the tram system interacts with the architecture, the people and even with the seasons. This work attempts to share the unspoken etiquette (on the trams and on the roads) and the seemingly normal activities that happen every day around the Ding Ding.s
English
Keywords: N4390-5098 Visual Arts. Exhibitions; Hong Kong